School Quality Culture as a Means of Shaping Students' Morals: Budaya Mutu Sekolah sebagai Sarana Pembentukan Akhlak Peserta Didik - Veninda Ramadhan; Hafidz (Academia Open, 2025)
General Background: Education plays a vital role in shaping students’ morality, supported not only by curriculum but also by the school’s cultural environment. Specific Background: Amid declining educational quality and increased moral issues such as student absenteeism and disrespectful behavior, schools need systematic approaches to character development. Knowledge Gap: Existing studies often focus on religious teachers' roles, overlooking the collective effort of all school members through a structured quality culture. Aims: This study investigates the implementation of school quality culture in shaping student morality at SMP Negeri 1 Masaran. Results: Using a qualitative case study approach, the findings reveal that moral improvement is fostered through habitual programs such as the "10 Budaya Malu," leadership modeling, consistent policy implementation, and involvement of all school elements. Novelty: Unlike prior research focusing on individual roles, this study emphasizes a whole-school approach that integrates quality culture as a systemic strategy for moral education. Implications: The success of moral development in schools requires collaborative participation from school leaders, educators, staff, students, and the broader community to establish a sustainable, value-oriented school environment.Highlight : Quality culture in schools shapes student character through consistent behavioral reinforcement. The principal's leadership and teacher role modeling are crucial in moral development. The "10 Budaya Malu" program fosters self-awareness and ethical behavior among students. Keywords : Quality Culture, Morals, Character Education, School Environment, Educational Leadership